1993
DOI: 10.1002/j.1460-2075.1993.tb05866.x
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplasmic tail of lysosomal acid phosphatase contains overlapping but distinct signals for basolateral sorting and rapid internalization in polarized MDCK cells.

Abstract: Lysosomal acid phosphatase (LAP) is synthesized as a type I membrane glycoprotein and targeted to lysosomes via the plasma membrane. Its cytoplasmic tail harbours a tyrosine‐containing signal for rapid internalization. Expression in Madine‐Darby canine kidney cells results in direct sorting to the basolateral cell surface, rapid endocytosis and delivery to lysosomes. In contrast, a deletion mutant lacking the cytoplasmic tail is delivered to the apical plasma membrane where it accumulates before it is slowly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
105
2
2

Year Published

1993
1993
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 48 publications
1
105
2
2
Order By: Relevance
“…31). However, it has been shown that the two sorting processes are differentially sensitive to various point mutations (28,49,50,51). The basolateral localization signal of the epidermal growth factor (48), transferrin (46), and immunoglobulin (15) receptors; the distal signal of the low density lipoprotein receptor (26); and the signal of vesicular stomatitis virus glycoprotein G (27,52) share with the FSH receptor the property of being independent of the internalization signal.…”
Section: The Basolateral Localization Signal Of the Fshr Is Differentmentioning
confidence: 99%
“…31). However, it has been shown that the two sorting processes are differentially sensitive to various point mutations (28,49,50,51). The basolateral localization signal of the epidermal growth factor (48), transferrin (46), and immunoglobulin (15) receptors; the distal signal of the low density lipoprotein receptor (26); and the signal of vesicular stomatitis virus glycoprotein G (27,52) share with the FSH receptor the property of being independent of the internalization signal.…”
Section: The Basolateral Localization Signal Of the Fshr Is Differentmentioning
confidence: 99%
“…Mutation of Tyr413 to Phe blocks endocytosis in MDCK cells, but not TGN to basolateral targeting, suggesting that the two types of signals can be separated (Prill et al, 1993). Analysis of the corresponding peptide by NMR indicates that this mutation destabilizes the /3-turn by about 25 % (Lehmann et al, 1992).…”
mentioning
confidence: 98%
“…26). Cytoplasmic determinants capable of targeting proteins from the TGN to the basolateral surface often overlap with tyrosine-based determinants required for clathrin-mediated endocytosis in several basolateral proteins (as found in the low density lipoprotein receptor (27), lysosomal glycoprotein 120 (28), lysosomal acid phosphatase (29), and the Fc receptor (28)). Detailed point mutational analysis within these overlapping signals (29,30) has shown that these two sorting activities can be separated, suggesting that basolateral targeting utilizes secondary structural motifs related to but not identical to the tyrosine-based endocytic signal which has been characterized to form a type 1 ␤-turn (31).…”
mentioning
confidence: 99%